2012
DOI: 10.1111/jzo.12001
|View full text |Cite
|
Sign up to set email alerts
|

On the perception, production and function of blue colouration in animals

Abstract: Bright colouration in animals has long attracted the attention of physicists, chemists and biologists. As such, studies on the functions of colours are interdisciplinary, focusing on the mechanisms of colour production and maintenance, the physical and chemical properties of the colour-producing elements, and visual systems and behaviour of potential receivers. Blue colouration has received a large share of research attention and is fascinating for several reasons: blue has been attributed to a very broad rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 154 publications
(207 reference statements)
0
29
0
Order By: Relevance
“…Throughout living organisms, blues are almost always produced by structural mechanisms, ranging from quasi-ordered structures to 1D, 2D, and 3D photonic crystals ( 23 , 24 ). Blue coloration in birds and insects is often produced by quasi-ordered or multilayered structures (that is, 1D photonic crystal), and we found that these two structural mechanisms also produce blue in tarantulas.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout living organisms, blues are almost always produced by structural mechanisms, ranging from quasi-ordered structures to 1D, 2D, and 3D photonic crystals ( 23 , 24 ). Blue coloration in birds and insects is often produced by quasi-ordered or multilayered structures (that is, 1D photonic crystal), and we found that these two structural mechanisms also produce blue in tarantulas.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of warning colors to date have largely focused on long‐wavelength, diffusely reflected colors (e.g., oranges, reds, and yellows; Umbers ). Stevens & Ruxton () propose that long‐wavelength colors may be more effective warning signals than short‐wavelength colors (e.g., ultraviolet, blue, and green) because they (1) are more conspicuous when viewed against green foliage, (2) are more reliably seen across a diversity of habitats, (3) permit distance‐dependent camouflage, and (4) are distinctive from colors displayed by profitable species.…”
Section: Introductionmentioning
confidence: 99%
“…This coloration is very vivid in live females, but is also observable to some degree in pinned specimens. Other colors, such as red, orange, and yellow, are due to the presence of carotenoids, but blue pigments are more rare because the required chemistry is more complex (Umbers, 2013). This coloration might be used by conspecifics for sex identification, although in Australia Umbers (2011) found that males of the chameleon grasshopper Kosciuscola tristis Sjöstedt change color in response to temperature.…”
Section: Discussionmentioning
confidence: 99%